In general whenever you have a "difference of squares", where both terms are squared and the sign in the middle is a minus:
a² - b²
The factorization is:
(a + b)(a - b) = a² - ab + ab - b² = a² - b²
In this case, a² = 16x², so a = 4x, and b² = y², so b = y.
(4x + y)(4x - y)
2006-12-26 10:40:56
·
answer #1
·
answered by Jim Burnell 6
·
1⤊
0⤋
16x^2 - y^2 = (4x + y)(4x - y). There is a very simple rule for this: a^2 - b^2 = (a + b)(a - b), where a and b could be anything. In your example, a is 4x and b is y.
2006-12-26 18:41:05
·
answer #2
·
answered by DavidK93 7
·
0⤊
0⤋
(16x^2 - y^2)
Difference of squares. Take the square root of each one, minused, then plused.
(4x - y) (4x + y)
2006-12-26 18:42:03
·
answer #3
·
answered by Puggy 7
·
1⤊
0⤋
16x^2 - y^2 = (4x)^2 - y^2
This is the difference of squares where
a^2-b^2=(a+b)(a-b)
Here a=4x and b=y
so you get (4x+y)(4x-y)
2006-12-26 18:41:47
·
answer #4
·
answered by Professor Maddie 4
·
1⤊
0⤋
16x^2-y^2=(4x+y)(4x-y)
2006-12-26 19:38:30
·
answer #5
·
answered by mu_do_in 3
·
0⤊
0⤋
16x^2-y^2
(4x+y)(4x-y)
2006-12-26 18:41:53
·
answer #6
·
answered by 7
·
0⤊
0⤋
(4x+y)(4x-y)
2006-12-27 18:36:30
·
answer #7
·
answered by etihad 3
·
0⤊
0⤋
(4x+y)(4x-y)
2006-12-26 19:00:33
·
answer #8
·
answered by raj 7
·
1⤊
0⤋